2019
DOI: 10.1186/s13643-019-1133-2
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite associated thrombotic microangiopathy: a protocol for the systematic review of clinical features, outcomes, and role of interventions

Abstract: Background Thrombotic microangiopathy is an uncommon complication of snake envenoming associated with a subset of snakebite cases presenting with venom-induced consumption coagulopathy. It presents with microangiopathic haemolytic anaemia and thrombocytopenia. Available studies are predominantly small retrospective observational studies only. Renal end organ injury appears common. It has variably been likened to either thrombotic thrombocytopenic purpura or atypical haemolytic uraemic syndrome. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The markers of microvascular hemolysis with anemia following snakebite envenomation are not specific 13 . MAHA was reported in two tiger snake envenomations that evolved with anemia, increased lactate dehydrogenase levels, increased serum indirect bilirubin levels, and fragmented red blood cells (schizocytes) in blood smears 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The markers of microvascular hemolysis with anemia following snakebite envenomation are not specific 13 . MAHA was reported in two tiger snake envenomations that evolved with anemia, increased lactate dehydrogenase levels, increased serum indirect bilirubin levels, and fragmented red blood cells (schizocytes) in blood smears 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma exchange and renal replacement treatment (RRT) after adequate antivenom administration are the main proposed treatments for TMA following snakebites 13,18 . Plasmapheresis is a nonspecific treatment used in many toxicological disorders to rapidly remove toxins from the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study performed in adult patients after Bothrops snakebite revealed a strong predisposition to development of coagulation abnormalities (aPTT) and AKI development [14]. However, snakebite-associated TMA is a poorly understood phenomenon thus further studies are required to improve the management of these patients [108].…”
Section: Venom-induced Consumption Coagulopathy (Vicc)mentioning
confidence: 99%